Organizational Leadership sebagai Paradigma Baru Tata Kelola Pondok Pesantren - Febi Febrianto; Mohammad Abdul Aziz Al-Wahedi (Yayasan Azhar Amanaa Yogyakarta, 2026)
The increasing complexity of Islamic boarding school (pesantren) organizations requires a leadership paradigm that is not solely dependent on the personal authority of the kyai, but is also capable of strengthening institutional governance through a sustainable organizational system. This study aims to analyze how Organizational Leadership is developed through the institutionalization of cultural leadership values to reinforce governance at Pondok Pesantren Nurul Jinan. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observations, and document analysis involving the pesantren caregiver, foundation leaders, institutional heads, core administrators, field coordinators, and organizational managers selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that organizational leadership is established through four interconnected processes: (1) strengthening cultural leadership values as the organizational foundation, (2) institutionalizing leadership values into organizational structures, work mechanisms, and governance systems, (3) distributing leadership across organizational levels according to functions and responsibilities, and (4) integrating cultural values with modern management practices to improve organizational effectiveness. These processes have enhanced coordination, accountability, collaboration, leadership regeneration, and institutional sustainability without diminishing the moral authority of the kyai. This study introduces Organizational Leadership as a new governance paradigm for Islamic boarding schools, emphasizing that leadership should be understood as an organizational capability embedded in institutional culture, structure, and governance systems rather than merely as an individual leader's attribute. The proposed model contributes to the development of governance theories for Islamic educational institutions by demonstrating that the institutionalization of cultural leadership values serves as a strategic mechanism for building professional, adaptive, and sustainable pesantren governance. Keywords: Organizational Leadership; Islamic Boarding School; Cultural Leadership; Institutionalization; Governance.